1997
DOI: 10.1002/(sici)1520-6793(199705)14:3<287::aid-mar5>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

A lifestyle analysis of female consumers in greater China

Abstract: This study compares the lifestyles of female consumers in Hong Kong, Taiwan, and China, which together make up Greater China. The investigation revealed that significant differences exist among the three groups of female consumers in nine different areas. These are (a) women's role and perception, (b) family orientation, (c) home cleanliness, (d) brand consciousness, (e) price consciousness, (f) self‐confidence, (g) addiction to work, (h) health consciousness, and (i) environmental consciousness. Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 19 publications
1
64
0
1
Order By: Relevance
“…They are more frequently and more willingly to pay higher prices for health or natural foods than Hong Kong females in terms of frequency and willingness. These results are consistent with those of Tai and Tam (1997), which suggested that women in Mainland China are more health conscious and willing to pay higher prices for green products than those in Hong Kong. Women in Shanghai are becoming more environment conscious and often search for information concerning green consumption, according to a survey conducted by Shanghai Women's Federation (4th July 2001, China Business Information Network).…”
Section: Article In Presssupporting
confidence: 87%
“…They are more frequently and more willingly to pay higher prices for health or natural foods than Hong Kong females in terms of frequency and willingness. These results are consistent with those of Tai and Tam (1997), which suggested that women in Mainland China are more health conscious and willing to pay higher prices for green products than those in Hong Kong. Women in Shanghai are becoming more environment conscious and often search for information concerning green consumption, according to a survey conducted by Shanghai Women's Federation (4th July 2001, China Business Information Network).…”
Section: Article In Presssupporting
confidence: 87%
“…Thus, a consumption of luxury goods is perceived as the major determinant of social position and prestige. The consensual and collective orientation and respect to those in power requires loyalty to dominant luxury brands (Robinson, 1996;Tai & Tam, 1997;Yau). The more positive the perception of a luxury good is the more likely it is desired and pursued by the Asian consumers (Phau & Prendergast, 2000).…”
Section: Cultural Influences On Luxury Shopping Behavior Of Asian Toumentioning
confidence: 99%
“…Specifically, any reference to China means mainland China, and does not include Taiwan, Hong Kong, or other parts of China. This is to avoid entangled discussions about the cultural, cognitive, and behavioral dissimilarities that exist between mainland China and these other areas (Tai and Tam, 1997;Inglehart and Baker, 2000 With respect to individuals typically found in China, the literature suggests that their values, cognitive and evaluative processes, and behaviors can be traced back to the ancient philosophies, beliefs, and teachings of Confucius, Buddha, and Tao (Hofstede, 1984;Markus and Kitayama, 1991;Watkins and Liu, 1996). In comparison, these aspects of individuals in Western cultures can be traced back to the ancient teachings of Socrates, Aristotle and Plato (Nakamura, 1960).…”
Section: Differences Between Chinese and Us Culturesmentioning
confidence: 99%